APLIKASI ASAP CAIR DARI KAYU LABAN (Vitex pubescens Vahl) UNTUK PENGAWETAN KAYU KARET - Prawira, Hendra; Oramahi, H A; Setyawati, Dina; Diba, Farah (JURNAL HUTAN LESTARI, 2013)
The objective of research was to evaluation the effect of application of liquid smoke from Vitex pubescens Vahl wood to rubber wood to inhibit the subterranean termites Coptotermes curvignathus Holmgren attack and to determine the level of concentration and optimum pyrolysis temperature of liquid smoke from Vitex pubescens Vahl wood to rubber wood to inhibit subterranean termites Coptotermes curvignathus Holmgren attack. The parameter of research was retention of liquid smoke to wood, termite mortality and weight loss rubber wood. The results showed that the highest retention of liquid smoke found at a concentration of 15% with a pyrolysis temperature of 400oC i.e. 0.0245 g/cm3. Mortality of termites in concentration of liquid smoke 10% with a pyrolisis temperature of 400oC resulted the highest mortality, i.e. 100% while the lowest weight loss of rubber wood was achieve on concentration of liquid smoke 15% with a pyrolysis temperature of 450oC i.e. 18.69%. Key words : liquid smoke, Vitex pubescens Vahl, rubber wood, Coptotermes curvignathus Holmgren